Amino acids digestibility of pelleted microparticle protein of fish meal and soybean meal in broiler chickens - Suthama, N.; Wibawa, P. J. (Diponegoro University, 2018)
Commom protein sources for poultry, fish meal and soybean meal, were ground to obtain reduced particle size. The particle was then dissolved in distilled water (1 : 4 w/v), and added with 2 mL virgin coconut oil for every 500 mL solution prior to ultrasound transducer (ultrasonic bath) treatment to obtain protein microparticle. Reducing particle size is one possible way to increase protein utilization.180 birds were used for forced feeding and 10 other birds were plotted for endogenous correction, when they were one month and a half old. Microparticle protein of both ingredients were tested separately in either mash or pelleted forms and compared to intact protein. Completely randomized design with 3 treatments (intact, mash, and pellet) and 6 replications (10 bidrs each) was arranged for the respective ingredient. Protein and essential amino acid digestibilities, and calcium retention were the parameters measured. Analysis of variance continued to Duncan test were applied to statistically evaluate the data. Pelleted microparticle protein of fish meal and soybean meal, respectively, resulted in significantly (P<0.05) highest protein and amino acids digestibilities, and Ca retention although lower disgestibility of fewer amino acids was found in mash form. In conclusion, pelleted form of microparticle protein of either fish meal or soybean meal improve protein and mostly amino acids digestibilities, and calcium retention in broiler.